Techno-economics analysis of biodiesel production from non-edible Reutealis trisperma oil / Teuku Meurah Indra Riayatsyah - Teuku Meurah, Indra Riayatsyah (2018)
The limitation of fossil fuel sources and environmental negative impact persuade scientists around the world to find a solution for this problem. Renewable fuel is one of the possible solutions to replace fossil fuel with cheaper process and can be produced in a short time. The productions of biodiesel from non-edible feedstocks are attracting more attention than in the past. Reutealis trisperma known as Philippine Tung is one of the non-edible feedstocks. The seeds contain a high percentage of oil content up to 51%. Thus, Reutealis trisperma seeds can be used as feedstock for biodiesel production. Therefore, the focus of this study is to investigate the biodiesel production from crude Reutealis trisperma oil using the ultrasonication method through esterification and transesterification process. Followed by, the assessment of the techno-economic and sensitivity analysis of biodiesel production from Reutealis trisperma as potential feedstock for biodiesel. Based on the result, the optimum conditions for the esterification and transesterification processes for Reutealis trisperma oil, an ultrasonic bath stirrer method with the maximum total power frequency of 40 kHz was used. The esterification process was performed using 2% (v/v) sulfuric acid (H2SO4), with a methanol-to-oil molar ratio of 60% (by vol.) at a temperature of 55 °C for 1 hour at 1000 rpm stirring speed. While the optimum condition for the transesterification process with a catalyst of 0.5 wt. % potassium hydroxide (KOH) and methanol-to-oil molar ratio of 60% (by vol.) at a temperature of 60 °C for 1.5 hours with the stirrer speed of 1000 rpm. This optimum condition gives the highest yield of 95.29% for the Reutealis trisperma biodiesel. Besides, the results showed that the ultrasonic bath stirrer method had more effect on the reaction time required than using the conventional method. The ultrasonic method reduced half of the conventional method reaction time. The properties of Reutealis trisperma biodiesel fulfilled ASTM D6751 and EN 14214 biodiesel standards which were viscosity: 6.48 mm2/s, density: 892 kg/m3, pour point: -2 ⁰C, cloud point: -1⁰C, flash point: 206.5⁰C, calorific value: 40.098 MJ/kg, acid value: 0.26 mg KOH/g. In addition, the life cycle cost and sensitivity analysis of Reutealis trisperma biodiesel were also analyzed. It was found that the total life cycle cost for a 50 ktons Reutealis trisperma biodiesel production plant with an operating period of 20 years was $710 million, yielding a payback period of 4.34 years. The largest share was the feedstock cost which accounted for 83% of total production cost. The most important finding from this study was that the biodiesel price can compete with fossil diesel if the policy of tax exemptions and subsidies can be fully applied. In conclusion, further research on the limitation of biodiesel production is recommended to be carried out before the biodiesel can be applied in internal combustion engine.